Produtos coloniais : resultado da produção na agroindústria “x” - Iaronka, Daniele (2022)
Family agroindustries take into account the traditions and customs of each region, which are passed down through generations, in order to maintain their roots. For this it is important to have an idea of the costs, expenses and profits of the property. The results of the agroindustry production of colonial products obtained in the first half of 2022 were analyzed. To carry out this work, a diagnostic research was used, being descriptive and mixed. Agroindústria has two products that were measured to find these results. The Italian type salami is equivalent to 91% of the raw material used in its specificities, while the frozen pork rib cut is equivalent to 9%. The variable costs of the raw material are equivalent to 42.03% in the Italian type salami and 39.31% in the frozen pork rib cut. The other costs and expenses are equivalent to 18.48% in relation to the Italian type salami and 19.28% in relation to the frozen pork rib cut, with an average profit percentage above 40%. It is suggested that the owners of the establishment maintain an up-to-date cost accounting so that the property will be well directed to continue having positive results.